The safety and efficacy of third- and fourth-generation cryoballoons for atrial fibrillation: a systematic review and meta-analysis - Zhang, Man-Li; Zhang, Chao; Peng, Jian-Yong; Xing, Shu-Qiao; Guo, Jian; Wei, Chen-Long; Zhang, Neng-Fang; Ma, En; Chen, Wen-Sheng (Frontiers in Cardiovascular Medicine, 2024)
Objectives: Increasing studies showed third-(CB3) and fourth-generation cryoballoon (CB4) were used to treat various types of atrial fibrillation (AF), but previous studies regarding the safety and efficacy of CB3 or CB4 ablation remained controversial conclusions. Therefore, a meta-analysis was performed to further evaluate the safety and efficacy of PVI using CB3 and CB4 in the treatment of AF.Methods: We searched PubMed, Cochrane Library, web of science, CNKI, Wanfang, VIP and Clinicaltrials.gov database up to Dec 2023 for qualified trials and data extraction according to inclusion and exclusion criteria. All analyses were carried out using the Review Manager 5.3 software.Results: Eventually, the meta-analysis included 13 observational studies consisting of 3281 subjects, and did not include a randomized controlled trial. Overall analyses indicated that CB3 significantly reduced total procedure time (WMD = -8.69 min, 95% CI=-15.45 -1.94 min, I 2 =93%), increased the PVI recording (RR=1.24, 95% CI= 1.03 1.49, I 2 =90%), and increased the mean nadir temperature of overall PVs (WMD =2.80 ℃, 95% CI=1.08 4.51 ℃, I 2 =89%) compared with CB2. Moreover, CB4 significantly reduced total procedure time (WMD = -14.50 min, 95% CI=-20.89 -8.11 min, I 2 =95%), reduced fluoroscopy time (WMD =-2.37 min, 95% CI=-4.28 -0.46 min, I 2 =95%), increased the PVI recording (RR=1.40, 95% CI=1.15 1.71, I 2 =90%), and increased the compared with CB2, respectively. Whereas time-to-isolation, success rate of PVI, AF recurrence and complication in CB3 and CB4 were not significant difference compared with CB2.These findings demonstrated that CB3 and CB4 tended to be more effective than CB2 in the treatment of AF, both with shorter procedure time, more PVI recording and similar safety endpoints.